Salt stress induces physiochemical alterations in rice grain composition and quality - Razzaq, Abdul; Ali, Arfan; Safdar, Luqman Bin; Zafar, Muhammad Mubashar; Rui, Yang; Shakeel, Amir; Shaukat, Abbad; Ashraf, Muhammad; Gong, Wankui; Yuan, Youlu (Journal of food science, 2020)
Salinity has drastic effects on plant growth and productivity and is one of the major factors responsible for crop yield losses throughout the agricultural soils of the world. The mechanisms of salinity tolerance in plants are regulated by a set of inherent multigenes and prevalent environmental factors, which bring about a myriad of metabolic changes in each plant part. The stress‐induced metabolic changes in the rice plant have been intensively studied, but extensively in plant parts such as stem, leaf, and root. However, little information exists in the literature about such stress‐induced architectural and physiological changes in rice grain, a premier staple food of a large proportion of human population. Thus, the current review comprehensively describes the effects of salinity stress on rice grain composition including changes in carbohydrate, protein, fat, and mineral contents. Elucidation of salinity induced changes in rice grain composition would help to understand whether or not a nutritious and healthy staple food is available to human population from rice grown under saline environments.